Intraoperative scoring system for grading severity of cholecystitis at laparoscopic cholecystectomy - Ansari, Shefa Tanwir; Bedi, Karamjot Singh; Sahu, Shantanu Kumar (International Surgery Journal, 2021)
Background: Various studies had been carried out to evaluate the risk of preoperative conversion in laparoscopic cholecystectomy. However, there was no grading or scoring of operative findings during surgery at present, making it difficult to compare the publications citing outcomes, including the conversion to open surgery. Sugrue in 2015 devised a scoring system based upon the intraoperative findings in Laparoscopic cholecystectomy. Aim of the study was to grade the severity of cholecystitis during laparoscopic cholecystectomy using intraoperative scoring system, to evaluate the spectrum of cholecystitis in cases of laparoscopic cholecystectomy in a tertiary center using the grades of intraoperative scores and to validate the scoring system devised by Michael Sugrue. Methods: This prospective cross sectional observatory study of 200 patients admitted for laparoscopic cholecystectomy was conducted in the Department of Surgery, Himalayan Institute of Medical Sciences, Dehradun, Uttarakhand, India over a period of 12 months. All patients directly planned for open cholecystectomy and carcinoma gall bladder were excluded from the study. Patients were subjected to the intra operative grading system for cholecystitis severity as devised by Micheal Sugrue and the grades were classified with a score of <2 - mild; 2 to 4 -moderate, 5– 7- severe and 8 to 10 – extreme. Results: The operative grading system showed a positive correlation with the severity of cholecystitis. Conclusions: Use of this intra-operative scoring system will help us to provide a trigger for a prompt early conversion to avoid intra-operative complications associated with difficult laparoscopic cholecystectomy.